Dengue Epidemic And Meteorological Factors In Central Region Of Malaysia Using Generalised Poisson Model - MOHAMAD YASIR, ANIS YASMIN; Che Him, Norziha (Enhanced Knowledge in Sciences and Technology, 2022)
Aedes aegypti mosquitoes are responsible for the transmission of dengue. DIR was often used in studies to represent insignificant factors, which may lead to unreliable conclusions. In this study, we aim to identify the weekly trend of DIR, to build a model of DIR, and then to explore which model best fits the data. Petaling, Hulu Langat, Gombak, and Klang are the four provinces we studied from 2010 to 2015. These statistics were collected over the course of several weeks and months from the Department of Statistics Malaysia (DOSM), the Department of Environment (DOE), and the Ministry of Health (MOH). Methods for this study included plotting weekly DIRs against time, Poisson GLMs, and statistical tests to select models, such as AIC, BIC, and deviance. A variety of socioeconomic and climate factors have also been collected in this study, and the climate factors have been lag-timed up to 1, 3, and 6 months. The weekly DIR trends also vary over time.